Functional contribution of coenzyme specificity-determining sites of 7α-hydroxysteroid dehydrogenase from Clostridium absonum. (October 2017) - Lou, Deshuai; Wang, Yue; Tan, Jun; Zhu, Liancai; Ji, Shunlin; Wang, Bochu
Graphical abstract: The natural coenzyme specificity-determining sites of 7α-hydroxysteroid dehydrogenase from Clostridium absonum allowed the greatest NADP(H) binding affinity (the lowest K m ), but not the best activity ( k cat ) toward coenzyme. Highlights: Functional contribution of CSDSs of CA 7α-HSDH was analysed. Mutant, R194A, with increased catalytic efficiency toward NADP + was probed. We confirmed the function of R38 for coenzyme anchoring. Abstract: Studies of the molecular determinants of coenzyme specificity help to reveal the structure-function relationship of enzymes, especially with regards to coenzyme specificity-determining sites (CSDSs) that usually mediate complex interactions. NADP(H)-dependent 7α-hydroxysteroid dehydrogenase from Clostridium absonum ( CA 7α-HSDH), a member of the short-chain dehydrogenase/reductase superfamily (SDRs), possesses positively charged CSDSs that mainly contain T15, R16, R38, and R194, forming complicated polar interactions with the adenosine ribose C2 phosphate group of NADP(H). The R38 residue is crucial for coenzyme anchoring, but the influence of the other residues on coenzyme utilization is still not clear. Hence, we performed alanine scanning mutagenesis and molecular dynamic (MD) simulations. The results suggest that the natural CSDSs have the greatest NADP(H)-binding affinity, but not the best activity ( k cat ) toward NADP + . Compared with the wild type and other mutants, the mutant R194A showed the highest catalytic efficiency ( k cat / K m ), which was more than three-times that of the wild type. MD simulation and kinetics analysis suggested that the importance of the CSDSs of CA 7α-HSDH should be in accordance with the following order R38 > T15 > R16 > R194, and S39 may have a supporting role in NADP(H) anchoring for mutants R16A/T194A and T15A/R16A/T194A.